Heat transfer enhancement of Al2O3-H2O nanofluids flowing through a micro heat sink with complex structure. (August 2015) - Zhai, Y.L.; Xia, G.D.; Liu, X.F.; Li, Y.F.
Abstract: The characteristic of flow and heat transfer of Al2 O3 -H2 O nanofluids flowing through a micro heat sink with complex structure under constant heat flux is investigated experimentally. The volume fraction and Reynolds number of Al2 O3 -H2 O nanofluids ranged from 0.1 vol.% to 1.0 vol.% and 100 to 700, respectively. Moreover, the effects of them on friction factor, Nusselt number, and thermal resistance are also considered. The results show that single phase model underestimates the friction factor and Nusselt number of nanofluids from the experiments. With increasing volume fraction and Reynolds number, both Nusselt number Nu and friction factor f of nanofluids increase while the average temperature at the bottom and thermal resistance decrease, as compared to deionized water. Moreover, new correlations of f and Nu are presented based on experimental data with the maximum deviation less than ± 5%. The performance evaluation plot shows that the higher slope of values, i.e., higher volume fraction of nanofluids, gives better comprehensive performance of heat transfer. The compound heat transfer enhancement techniques, i.e., cavities in the micro heat sink and nanofluids can obviously enhance heat transfer.